2017
DOI: 10.1152/jn.00145.2017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the VTA and LC response to methylphenidate: a concomitant behavioral and neuronal study of adolescent male rats

Abstract: Methylphenidate (MPD), also known as Ritalin, is a psychostimulant used to treat attention deficit hyperactivity disorder. However, it is increasingly being misused by normal adolescents for recreation and academic advantage. Therefore, it is important to elucidate the behavioral and neurophysiological effects of MPD in normal subjects. MPD inhibits the reuptake of catecholamines, mainly found in the ventral tegmental area (VTA) and locus coeruleus (LC). The VTA and LC normally mediate attention, motivation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 104 publications
0
12
0
1
Order By: Relevance
“…Although we found significant differences in just this first exposure, we believe much more can be gained from looking at a chronic exposure to MPD, as we would then be able to make conclusions about the differences in tolerance and sensitization in the various animal groups we studied. Additionally, many studies have shown the concordance between behavioral and electrophysiologic data from brain structures implicated in the reward pathway [41,4,5] . This presents another area for comparison between sex, age and strain.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although we found significant differences in just this first exposure, we believe much more can be gained from looking at a chronic exposure to MPD, as we would then be able to make conclusions about the differences in tolerance and sensitization in the various animal groups we studied. Additionally, many studies have shown the concordance between behavioral and electrophysiologic data from brain structures implicated in the reward pathway [41,4,5] . This presents another area for comparison between sex, age and strain.…”
Section: Discussionmentioning
confidence: 95%
“…Open field locomotion behaviors represent the interaction of the whole animal within the experimental situation. The details of the procedure are well established and previously published [41,42,4,5,43,36,40] . Each interruption from each sensor was counted and cumulative counts were compiled by the Accuscan Analyzer (Columbus, OH, USA).…”
Section: Behavioral Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting on experimental day 9 (ED 9-MPD), daily injections of 2.5 mg/kg MPD (Mallinckrodt, Hazelwood MO) dissolved in 0.8 mL of 0.9% saline were administer for 6 consecutive days (ED 9-MPD to ED 14-MPD), and activity recorded for 120 minutes post-injection. This dose of 2.5 mg/kg MPD has been shown to be sufficient to elicit behavioral sensitization in rats in previous doseresponse experiments [27][28][29]48,51,[61][62][63][64][65][66][67][68]. For the next 3 days (ED 15-17), animals received no injections (the washout period).…”
Section: Experimental Procedures (Table 1)mentioning
confidence: 99%
“…Our aim was to test whether repeated treatment with these doses, which are commonly used in the literature of animal models of ADHD, would alter subsequent ethanol self-administration during adolescence and assess potential behavioral and neurochemical correlates of this effect. More in detail, the MPH dose employed is in the upper range of doses employed in animal models of ADHD (Karim, Reyes-Vazquez, & Dafny, 2017;Venkataraman, Claussen, & Dafny, 2017); and doses equal or lower than 10.0 mg/kg MPH have been found to evoke changes in MPH-induced motor activity (i.e., behavioral sensitization or tolerance; Chong, Claussen, & Dafny, 2012;Frolov, Reyes-Vasquez, & Dafny, 2015;Gaytan, Nason, Alagugurusamy, Swann, & Dafny, 2000;Gaytan, Yang, Swann, & Dafny, 2000). Similarly, we employed a dose of AMPH that has been repeatedly employed in the assessment of AMPH-induced behavioral sensitization and has been shown to yield this phenomenon in adolescent mice (Kameda et al, 2011).…”
Section: Drugsmentioning
confidence: 99%